2013
DOI: 10.21829/myb.2013.192339
|View full text |Cite
|
Sign up to set email alerts
|

Análisis espacio-temporal de la ocurrencia de incendios forestales en Durango, México

Abstract: Los incendios forestales representan un gran problema en la pérdida de biodiversidad, en laemisión de gases efecto invernadero y en la modificación de los flujos hídricos. En México, los incendiosson causados en su mayoría por la acción del hombre, por lo que factores como la accesibilidad,distancia a caminos y poblados, entre otros, influyen en su frecuencia y distribución. Utilizando unabase de datos de la Conafor, periodo 2000-2011, se realizó un análisis espacio-temporal de la ocurrenciade los incendios fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 0 publications
1
6
0
10
Order By: Relevance
“…Fire ignitions have been reported to have specific spatial occurrence patterns (e.g., Butry 2005, McRae andSharples 2015), which result from different environmental or socioeconomic factors (Yang et al 2007, Pérez-Verdín et al 2013, Salvati et al 2014. Some studies have shown that spatial patterns of fire hotspots are related to their causes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fire ignitions have been reported to have specific spatial occurrence patterns (e.g., Butry 2005, McRae andSharples 2015), which result from different environmental or socioeconomic factors (Yang et al 2007, Pérez-Verdín et al 2013, Salvati et al 2014. Some studies have shown that spatial patterns of fire hotspots are related to their causes.…”
Section: Discussionmentioning
confidence: 99%
“…A spatiotemporal analysis of annual series for the two databases was carried out, to test the temporal and spatial autocorrelation in stochastic phenomena (Pérez-Verdín et al 2013). Whether fire occurrence in a particular year was statistically related to that of the previous year was evaluated through autoregressive models (up to four lags).…”
Section: Methodsmentioning
confidence: 99%
“…In Mexico, Manzo-Delgado et al [49,50] demonstrated the potential of the temporal evolution of NDVI-based indices as indicators of fuel drought and associated fire risk for the central region of the country. Some studies have evaluated the role of weather variables such as precipitation or temperature on fire occurrence risk (e.g., [51][52][53]), mainly at regional or local scales. The work of Pompa-Garcia et al [54] explored the association between fire records and the Standardized Precipitation-Evapotranspiration Index (SPEI) drought index, finding that the relationships of drought and fire vary by regions in the country.…”
Section: Introductionmentioning
confidence: 99%
“…La construcción del modelo espacial es de las pocas aplicaciones de modelado espacial en el contexto de predicción de zonas potenciales de incendios (Mandallaz y Ye, 1997;García et al, 1999;Muñoz et al, 2005;Pompa-García et al, 2013;Pérez-Verdín, 2013), y es el único hasta el momento que integra variables de CMIP5.…”
Section: Resultados Y Discusiónunclassified